Determinants of Hardiness among Representatives of Three Generations in Modern Russia - Вера А. Федотова (Российский психологический журнал, 2020)
Introduction. Generational differences have been scarcely investigated. The factors that help individuals to cope with stressful factors and increasing tension are worth consideration in the context of present-day reality. This study addresses the predictors of hardiness in different generations of Russians.